2014
DOI: 10.3748/wjg.v20.i38.14004
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance enterography in refractory iron deficiency anemia: A pictorial overview

Abstract: MRE is a non-invasive and effective alternative for evaluating possible malignancies of the small intestines and can serve as a guide for a second-look endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…However, this review did not distinguish individuals with overt versus occult bleeding. The diagnostic yield of small bowel imaging speci cally in those without overt bleeding is likely much lower, as evidenced by a study conducted by Cengic et al, in which MRE detected positive ndings in 7.5% of patients with refractory iron de ciency anemia, including 2 patients with malignancy (1 adenocarcinoma, 1 lymphoma), 1 with Crohn's disease, and 1 with antral gastritis that was later seen on repeat gastroscopy [10]. To our knowledge, no other studies have reported detection rates of CSLs in small bowel investigations among patients with IDA without overt bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this review did not distinguish individuals with overt versus occult bleeding. The diagnostic yield of small bowel imaging speci cally in those without overt bleeding is likely much lower, as evidenced by a study conducted by Cengic et al, in which MRE detected positive ndings in 7.5% of patients with refractory iron de ciency anemia, including 2 patients with malignancy (1 adenocarcinoma, 1 lymphoma), 1 with Crohn's disease, and 1 with antral gastritis that was later seen on repeat gastroscopy [10]. To our knowledge, no other studies have reported detection rates of CSLs in small bowel investigations among patients with IDA without overt bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…While historical studies have reported rates of CSLs in the small bowel in the context of IDA ranging from 32% to 78% [9] following negative EGD and colonoscopy, most of these studies included patients with overt and occult bleeding. The few studies that have speci cally evaluated obscure occult IDA cite much lower rates of positive ndings, with MR enterography being normal in 92.5% of subjects in one study [10]. Nevertheless, many practitioners may feel compelled to proceed with small bowel investigations, particularly in elderly individuals, for fear of missing small bowel cancers, Crohn's disease or vascular ectasias that are at risk of re-bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…It can detect the mural thickening (>4 mm) and mass lesion of the small bowel. These lesions could be secondary to inflammatory and benign conditions (like Crohn's disease, adenoma, lipoma, fibroepithelial polyps) or malignant conditions (like neuroendocrine tumors, GIST, adenocarcinoma, lymphoma, and Peutz-Jeghers syndrome) [33,34].…”
Section: Mrementioning
confidence: 99%
“…After a 4–6 h fast, 1000–2000 cc of a biphasic water-based oral contrast similar to the ones used during CTE is administered, often with metoclopramide (10–20 mg po), followed by a gadolinium-based intravenous contrast (0.65 mg/kg) together with either hyoscine butylbromide (20 mg iv) or glucagon (0.5 mg iv). 5 , 6 …”
Section: Technical Characteristicsmentioning
confidence: 99%
“…Few studies have reported on the usefulness of MRE in the context of OGIB, but its use it limited by a lower spatial resolution than CTE, 5 reduced availability in the urgent setting, 6 and cost. 69 When compared to SBCE, MRE demonstrated a significantly inferior diagnostic yield (53% vs. 21%).…”
Section: Obscure Gastrointestinal Bleedingmentioning
confidence: 99%